Educação e entretenimento: estudo de objetos de aprendizagem no contexto da televisão interativa - Gomes, Flávia Maria [UNESP] (2014)
Analyze in this work, in an exploratory manner, as in contemporary society, information and knowledge could be disseminated appropriating latest technological resources, a means of mass communication, particularly the Digital Television (DTV). For this, we discuss the possibility of using learning objects (LO) to viewers during conventional programming DTV, expanding educational opportunities with informal and non-formal activities. It is understood that learning can happen through formal education (as in shools), information (such as in museums or LO) or throgh non-formal education (passed from parents to children, for example). Because there are many LO repositories free on the internet, the costs would be reduced because there would be no need to produce educational content only for that use. DTV, as a communication vehicle of the masses in our country, could provide contextualized educational content to programming, so that the viewers have options to have access to systematized knowledge, with the possibility of using the internet as a return channel, among many. Am example application is designed to demonstrate some practical suggestions for interaction between LO geography and users of DTV on routine schedules